2012
DOI: 10.1080/1047840x.2012.651387
|View full text |Cite
|
Sign up to set email alerts
|

Mind Perception Is the Essence of Morality

Abstract: Mind perception entails ascribing mental capacities to other entities, whereas moral judgment entails labeling entities as good or bad or actions as right or wrong. We suggest that mind perception is the essence of moral judgment. In particular, we suggest that moral judgment is rooted in a cognitive template of two perceived minds—a moral dyad of an intentional agent and a suffering moral patient. Diverse lines of research support dyadic morality. First, perceptions of mind are linked to moral judgments: dime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

27
656
4
12

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 712 publications
(718 citation statements)
references
References 238 publications
27
656
4
12
Order By: Relevance
“…In their influential model, Gray and colleagues (2007) demonstrated that people perceive others' minds as being comprised of two distinct and conceptually orthogonal dimensions: agency (i.e., the capacity for higher order cognitions, such as planning, communicating, and remembering) and experience (i.e., the capacity for experiencing sensations and drive-states such as pleasure, pain, and hunger). Individuals high in agency can act with intention and thus are seen as moral agents, capable of enacting right and wrong, whereas individuals high in experience are seen as moral patients, capable of being acted upon (Gray, Knobe, Sheskin, Bloom, & Barrett, 2011;Gray, Young, & Waytz, 2012). Because high fWHR targets are often seen as impulsively aggressive (Geniole et al, 2015), we hypothesized that they would be ascribed minds that are low in agency.…”
Section: Studymentioning
confidence: 99%
“…In their influential model, Gray and colleagues (2007) demonstrated that people perceive others' minds as being comprised of two distinct and conceptually orthogonal dimensions: agency (i.e., the capacity for higher order cognitions, such as planning, communicating, and remembering) and experience (i.e., the capacity for experiencing sensations and drive-states such as pleasure, pain, and hunger). Individuals high in agency can act with intention and thus are seen as moral agents, capable of enacting right and wrong, whereas individuals high in experience are seen as moral patients, capable of being acted upon (Gray, Knobe, Sheskin, Bloom, & Barrett, 2011;Gray, Young, & Waytz, 2012). Because high fWHR targets are often seen as impulsively aggressive (Geniole et al, 2015), we hypothesized that they would be ascribed minds that are low in agency.…”
Section: Studymentioning
confidence: 99%
“…Climate change carries terrible potential for destruction and is therefore an issue ripe for moralization through judgments of harm caused by energy waste (for a discussion of other barriers to moralization of climate change, see Markowitz & Shariff, 2012). Harm to others (e.g., pain, injury, death, property loss) is central to most theories of morality and an important source of moral judgment (Graham, Haidt, & Nosek, 2009;Gray, Young, & Waytz, 2012;Kohlberg, 1969;Nucci, 1981;Piaget 1932Piaget /1965Shweder, 1990;Turiel, Killen, & Helwig, 1987). For example, acts thought to help or harm others (e.g., reckless driving) are more likely to be seen as moral (Gray & Schein, 2012; and evoke stronger moral judgment (Young & Saxe, 2011;Uhlmann & Zhu, 2014).…”
Section: Moralization and Demoralizationmentioning
confidence: 99%
“…To not harm others is widely considered the most basic element of human morality (Cushman et al, 2006;Haidt, 2007;Gray et al, 2012). There is substantial evidence highlighting the role that aversion to harm plays in moral judgments (Blair, 1995;Cushman et al, 2012;Crockett, 2013;Schein and Ward, 2014).…”
mentioning
confidence: 99%